PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA ULUN UBUD RESORT & SPA GIANYAR - Anak Agung Lilis Antika; Putu Agus Eka Rismawan; Sapta Rini Widyawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Job satisfaction is an important thing that a company must pay attention to. The more aspects that suit the individual's wishes in their work, the higher the level of job satisfaction that will be felt. Job satisfaction can improve employee performance by paying attention to the work environment that the company pays attention to, the work motivation provided by the company and the work stress that is handled within the company. This research aims to determine the influence of the work environment, work motivation and work stress on employee job satisfaction at Ulun Ubud Resort & Spa Gianyar. The population in this study were all employees of Ulun Ubud Resort & Spa Gianyar, totaling 38 people. Determining the number of samples using a saturated sampling technique with a sample size of 38 employees. The data analysis technique used was multiple linear regression analysis. The test results show that the work environment and work motivation have a positive and significant effect on employee job satisfaction, while work stress has a negative and significant effect on employee job satisfaction at Ulun Ubud Resort & Spa Gianyar.